Sphingosine‐1‐phosphate controls endothelial sphingolipid homeostasis via ORMDL. (21st November 2022) - Sasset, Linda; Chowdhury, Kamrul H; Manzo, Onorina L; Rubinelli, Luisa; Konrad, Csaba; Maschek, J Alan; Manfredi, Giovanni; Holland, William L; Di Lorenzo, Annarita
Abstract: Disruption of sphingolipid homeostasis and signaling has been implicated in diabetes, cancer, cardiometabolic, and neurodegenerative disorders. Yet, mechanisms governing cellular sensing and regulation of sphingolipid homeostasis remain largely unknown. In yeast, serine palmitoyltransferase, catalyzing the first and rate‐limiting step of sphingolipid de novo biosynthesis, is negatively regulated by Orm1 and 2. Lowering sphingolipids triggers Orms phosphorylation, upregulation of serine palmitoyltransferase activity and sphingolipid de novo biosynthesis. However, mammalian orthologs ORMDLs lack the N‐terminus hosting the phosphosites. Thus, which sphingolipid(s) are sensed by the cells, and mechanisms of homeostasis remain largely unknown. Here, we identify sphingosine‐1‐phosphate (S1P) as key sphingolipid sensed by cells via S1PRs to maintain homeostasis. The increase in S1P‐S1PR signaling stabilizes ORMDLs, restraining SPT activity. Mechanistically, the hydroxylation of ORMDLs at Pro137 allows a constitutive degradation of ORMDLs via ubiquitin‐proteasome pathway, preserving SPT activity. Disrupting S1PR/ORMDL axis results in ceramide accrual, mitochondrial dysfunction, impaired signal transduction, all underlying endothelial dysfunction, early event in the onset of cardio‐ and cerebrovascular diseases. Our discovery may provide the molecular basis for therapeutic intervention restoring sphingolipid homeostasis. Synopsis: Dysregulation of sphingolipid metabolism contributes to disease states. This study reveals how mammalian endothelial cells sense sphingolipids and how they regulate their biosynthesis, with potential therapeutic implications. At steady state, the hydroxylation of P137 of ORMDL promotes ORMDL's ubiquitination and proteasomal degradation. S1P signaling via S1PR1, 3 stabilizes ORMDL by inhibiting its hydroxylation, resulting in the suppression of SPT activity and sphingolipid biosynthesis. Disruption of the S1P‐S1PRs‐ORMDLs negative feedback on SPT causes ceramide accrual, mitochondrial dysfunction, impaired signal transduction and vascular tone regulation, all underlying endothelial dysfunction Abstract : Dysregulation of sphingolipid metabolism contributes to disease states. This study reveals how mammalian endothelial cells sense sphingolipids and how they regulate their biosynthesis, with potential therapeutic implications.